Bereitstellung einer Smartphone-Variante von eGENA, der elektronischen Gedächtnis- und Entscheidungshilfe für Notfälle in der Anästhesiologie - Richter, T.; Baus, J.; Eismann, H.; Happel, O.; Heller, A. R.; Neuhaus, C.; Weinert, M.; St. Pierre, Michael (Anästhesiologie & Intensivmedizin, 2021)
The German Cognitive Aid Working Group of the Professional Association of German Anaesthesiologists (BDA) and the German Society of Anaesthesiology and Intensive Care Medicine (DGAI) developed ‘eGENA’, a browser-based cognitive aid for intra- and postoperative emergencies using an iterative user-centred design process according to DIN EN ISO 9241-210. The app is available for free download. We intentionally designed the progressive-web-application eGENA to support the presentation in a landscape format (e. g. PC-screen, tablet) which would allow all team members to jointly read the information. As a result, a meaningful presentation on the display of mobile phones was not possible until recently. We developed an optimized display for smartphones to close the existing gap of suitable devices and to promote user acceptance of and familiarity with eGENA. Currently, a number of German anaesthesia departments encounter difficulties in implementing eGENA because their IT-infrastructure is either insufficiently equipped or too restrictive. As many anaesthetists carry a mobile device with them at work, the provision of a smartphone version may help to increase the availability of and familiarity with eGENA and ultimately may foster its clinical application during emergencies in anaesthesia.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Cognitive aid; Crisis management; Decision-making; Memory; Web application